2019
DOI: 10.1038/s41588-019-0519-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of venous thromboembolism identifies new risk loci and genetic overlap with arterial vascular disease

Abstract: Venous thromboembolism (VTE) is a significant cause of mortality 1 , yet its genetic determinants remain incompletely defined. We performed a discovery genome-wide association study in the Million Veteran Program and UK Biobank testing ~13 million DNA sequence variants for association with VTE (26,066 cases; 624,053 controls) and meta-analyzed both studies, followed by independent replication with up to 17,672 VTE cases and 167,295 controls. We identified 22 novel loci, bringing the total number of VTE-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
221
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(237 citation statements)
references
References 51 publications
16
221
0
Order By: Relevance
“…We first tested whether any of the cis-pQTLs or proxies in high LD (r²>0.8) have been reported in the GWAS catalogue and identified links between genetically verified drug targets and corresponding indications for lead cis-pQTLs at F2 (rs1799963 associated with venous thrombosis 28 ), IL6R (rs2228145 with rheumatoid arthritis 29 ), and PLG (rs4252185 associated with coronary artery disease 30 ).…”
Section: Linking Cis-pqtls To Clinical Outcomesmentioning
confidence: 99%
“…We first tested whether any of the cis-pQTLs or proxies in high LD (r²>0.8) have been reported in the GWAS catalogue and identified links between genetically verified drug targets and corresponding indications for lead cis-pQTLs at F2 (rs1799963 associated with venous thrombosis 28 ), IL6R (rs2228145 with rheumatoid arthritis 29 ), and PLG (rs4252185 associated with coronary artery disease 30 ).…”
Section: Linking Cis-pqtls To Clinical Outcomesmentioning
confidence: 99%
“…PAI-1 inhibits fibrinolysis by cleaving tPA and uPA via the serine protease mechanism [198]. This gene's expression is strongly linked to VTE within large Genome Wide Association Studies (GWAS) and mice overexpressing PAI-1 form 50% larger thrombus than mice with PAI-1 deficiency [199][200][201]. However, animal studies of PAI-1 inhibition have been mixed.…”
Section: Fibrinolysismentioning
confidence: 99%
“…Interestingly, Klarin et al (2017 ) recently reported an association between the T allele of rs6993770 and decreased risk of venous thromboembolism (VTE). They postulated that the underlying mechanism is a ZFPM2 mediated decrease in the plasma concentration of the principal inhibitor of plasminogen activator PAI-1, which is encoded by SERPINE1 (Klarin et al 2019) . The notion that lower levels of plasma PAI-1 cause a reduced risk of VTE is biologically plausible.…”
Section: Evidence That Zfpm2 Is a Regulator Of Platelet α-Granularitymentioning
confidence: 99%